Rigorous Design Optimization of a Fiber-Enabled Polarimetric Waveguide Interferometer for Biosensing - Samuel M. Hormann; Gandolf Feigl; Jakob W. Hinum-Wagner; Alexander Bergmann (IEEE Photonics Journal)
Integrated photonic sensors have gained significant attention for biosensing applications. An especially potent design is the polarimetric waveguide interferometer, which utilizes polarization diversity for effective self-referencing. However, its implementations are held back by the need for bulky free-space optics or unreliable waveguide junctions for polarization handling. To overcome these limitations, we propose a novel concept for a compact photonic system that employs edge couplers to excite both polarizations from an optical fiber and an in-line polarizer to obtain the phase information in the fiber-based readout. Additionally, we improve the waveguide design methodology to minimize the limit of detection through balancing sensitivity with optical loss. To this end, we create a unified perturbative approach based on atomic force microscopy and ellipsometry data to model sensitivity, surface-roughness-induced scattering, absorption, and radiation. We then incorporate the coupling efficiency into a figure of merit for the combined system. Thus, we optimize the geometry of a strip waveguide on a CMOS-foundry-sourced silicon nitride platform for biosensing. Through exhaustive screening of the design space, we discover that polarization diversity simultaneously leverages high sensitivity and low overlap with sidewall roughness. Further, we present designs that eliminate the phase signal from two major noise sources: thermal and bulk refractive index fluctuations. Finally, we provide design recommendations and achieve a 5.2-fold improvement over a comparable bimodal waveguide interferometer. Thus, our aim is to design a robust, compact, sensitive, and cost-effective polarimetric waveguide interferometer through an efficient concept and an optimized design.